2010
DOI: 10.4236/health.2010.22020
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction (AMI) and Intermediate Coronary Syndrome (ICS)

Abstract: In recent studies it was shown that blood coagulation and inflammation markers are raising at high geomagnetic activity; acute myocardial infarction and all his subtypes, mostly related to atheromatous plaque disruption with higher Cosmic Ray (Neutron) activity. The aim of this study was to explore AMI and ICS differences by concomitant physical conditions, accompanying each of these acute coronary syndromes. (r=0.23, p=0.048). ICS was not correlated with these two parameters, but show significant links to GM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The results of this study support previous cosmobiological research, which generally pointed to a link between cardiac events such as cardiac arrhythmias, sudden cardiac death, acute myocardial infarction, and cerebral stroke with levels of cosmic ray, solar, and geomagnetic activity . Our study also extends these findings to the most dangerous form of cardiac arrhythmia‐electric heart storms, showing a significant relationship between the time of occurrence of electrical heart storms detected by implanted defibrillators and relatively high levels of cosmic ray (neutron) activity.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study support previous cosmobiological research, which generally pointed to a link between cardiac events such as cardiac arrhythmias, sudden cardiac death, acute myocardial infarction, and cerebral stroke with levels of cosmic ray, solar, and geomagnetic activity . Our study also extends these findings to the most dangerous form of cardiac arrhythmia‐electric heart storms, showing a significant relationship between the time of occurrence of electrical heart storms detected by implanted defibrillators and relatively high levels of cosmic ray (neutron) activity.…”
Section: Discussionsupporting
confidence: 90%
“…AMI is related to neutron activity, and ICS is related more to GMA (31) . AMI is related to neutron activity, and ICS is related more to GMA (31) .…”
Section: Discussionmentioning
confidence: 99%
“…The different mechanisms of AMI and other forms of acute coronary insuffi ciency -intermediate coronary syndrome -were shown in another study (43) , which showed that AMI is more related to CRA (neutron) and intermediate coronary syndrome is more related to GMA (43) . However, extreme levels of CRA (neutron) on the one hand and SA and GMA on the other hand are two sides of the equilibrium paradigm in clinical cosmobiology (44,45) . As shown in this study, in the middle latitudes in recent years, the prevailing physical conditions are connected with predominantly lower levels of SA and GMA and higher levels of CRA (neutron).…”
Section: Discussionmentioning
confidence: 99%